Edukasi dan Pelatihan Pemanfaatan Sabut Kelapa Sebagai Tanaman Hias Kokedama pada Siswa MA Islamiyah Senori, Tuban - Lisa Dwifani Indarwati; Nurenik Nurenik; Adi Rastono; Masrur Muzadi; Faza Yasmin Saidah (Buletin Dharmas Andalas, 2026)
Coconut coir is an abundant agricultural by-product that, if not properly utilized, has the potential to become waste. One alternative to increase its economic value is to use coconut coir as a growing medium for ornamental plants using the “kokedama” technique. This community service program aimed to enhance students' knowledge and practical skills in utilizing coconut coir as a growing medium for economically valuable “kokedama”, while also fostering an entrepreneurial mindset among young people. The participants consisted of 40 students from MA Islamiyah Senori, Tuban. The program was implemented using a participatory approach through hands-on activities, including preparation, educational sessions, demonstrations, practical training, and evaluation using a post-test consisting of 15 multiple-choice questions. The results showed that the students actively and enthusiastically participated in all stages of the program. Furthermore, the post-test results indicated that the participants achieved a high level of understanding after completing the training. This was reflected in a mean post-test score of 13.33 out of a maximum score of 15, corresponding to a mastery level of approximately 88.9%, with relatively low variation among participants' scores.